Electric field induced biaxiality and the electro-optic effect in a bent-core nematic liquid crystal - VIJ, JAGDISH; PANARIN, YURI; MANNA, UTTAM (My University, 2010)
We report the observation of a biaxial nematic phase in a bent-core molecular system using polarizing microscopy, electro-optics, and dielectric spectroscopy, where we find that the biaxiality exists on a microscopic scale. An application of electric field induces a macroscopic biaxiality and in consequence gives rise to electro-optic switching. This electro-optic effect shows significant potential in applications for displays due to its fast high-contrast response. The observed electro-optic switching is explained in terms of the interaction of the ferroelectric clusters with the electric field.
PUBLISHED
Keywords: Electronic & Electrical Engineering